THE USE OF GROUP TESTS TO PROMOTE COLLABORATION AND LEARNING: DO THEY WORK? - Gilbride, Kimberley Ann (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2020)
The research was carried out to determine whether the use of group tests for undergraduate science students to augment lecture material in a second-year core course in microbiology would improve the retention of material on a subsequent regular mid-term/final exam. On three separate occasions, the students were asked to complete short multiple-choice tests individually and then were asked to get together in groups of 4 to re-answer the same questions. The discussions they had in the groups improved their individual marks by 10.9% in the first test, 14.5% in the second test and 20.9% in the third test. Overall, the class average was 2.5% better than the previous year. The majority of the students indicated that the group tests improved their understanding and helped them to learn the lecture material.